Confucius and the Analects - edited by Bryan W. Van Norden (Oxford University Press, 2002)
Confucius is one of the most influential figures--as historical individual and as symbol--in world history; and the Analects, the sayings attributed to Confucius and his disciples, is a classic of world literature. Nonetheless, how to understand both figure and text is constantly under dispute. Surprisingly, this volume is the first and only anthology on these topics in English. Here, contributors apply a variety of different methodologies (including philosophical, phililogical, and religious) and address a number of important topics, from Confucius and Western "virtue ethics" to Confucius' attitude toward women to the historical composition of the text of the Analects. Scholars will appreciate the rigor of these essays, while students and beginners will find them accessible and engaging